Organic electrolyte hybridized ZnO as the electron transport layer for inverted polymer solar cells - Kim, Dong Geun; Kim, Youn Hwan; Maduwu, Ratna Dewi; Jin, Ho Cheol; Moon, Doo Kyung; Kim, Joo Hyun (Journal of industrial and engineering chemistry (Seoul, Korea), 2018)
[Display omitted] •Small molecular organic electrolyte for dopant.•Electrolyte doped ZnO a the electron transport layer.•Enhancement of the PCE mainly resulted from the Jsc improvement. Small molecular organic electrolyte; N,N,N,N,N,N-hexakis(2-hydroxyethyl)butane-1,4-diaminium bromide (C4), doped ZnO is prepared by a typical sol–gel process and used as the for an electron transport layer in inverted polymer solar cells (PSCs). The electron mobility of the doped ZnO is comparable to that of pristine ZnO because the crystallinity of the ZnO layer is not significantly affected by the doping process. The Kelvin probe microscopy measurements employ that the work function of doped ZnO are −4.0eV, which is higher than that of pristine ZnO (−4.5eV). This is due to that the formation of interface dipole at the interface between the ZnO layer and the active layer by unreacted hydroxyl groups and quaternary ammonium bromide. As a result, inverted PSC based on C4 doped ZnO exhibit the power conversion efficiency (PCE) up to 8.87%, which is a significant improvement over the device based on pristine ZnO (PCE=7.4%). Note that the main contribution to the enhancement of the PCE is from the improvement of the Jsc.